RESULTS OF EMERGENCY OSTEOPERFORATION IN ACUTE POSTOPERATIVE SPONDYLODISCITIS - Tilyakov Aziz Burievich; Nazarov Sarboz Parda ugli; Umirov Abdullo Sulaimonovich (Scholar Express Journals, 2022)
A compression fracture of the spine is the most pressing problem of modern vertebrology and orthopaedic surgery. Traumatic injuries resulting in damage to the structural integrity of the thoracolumbar spine can lead to a number of serious health consequences. Only the quickest and most adequate fixation, unloading of the injured segment and the formation of a strong muscular corset give a real chance of full recovery.
Keywords: Spondylitis; spondylodiscitis; biopsy; osteoperforation